1991
DOI: 10.1002/bjs.1800780205
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell tumour: Clinical behaviour and treatment

Abstract: We have reviewed 30 reports of Merkel cell tumour and described a further five cases in order to establish a database and from this more clearly define the biology of this tumour, prognostic factors that govern outcome, and optimal management. After excision alone of the primary lesion, local recurrence occurred in 39 per cent of patients and regional failure occurred in 46 per cent. In contrast, in patients treated by excision plus prophylactic treatment (adjuvant node dissection and/or adjuvant radiation), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
3
11

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(163 citation statements)
references
References 34 publications
3
146
3
11
Order By: Relevance
“…[3][4][5][6][7] Thirty-three patients (62%) registered on this study had involved nodes (stage II) at presentation. This contrasts with the literature where the reported incidence of nodes at presentation varied from 9% to 33%, [3][4][5][8][9][10][11] and confirms the particularly poor prognostic profile of patients in this trial (being at high risk of disseminated disease).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…[3][4][5][6][7] Thirty-three patients (62%) registered on this study had involved nodes (stage II) at presentation. This contrasts with the literature where the reported incidence of nodes at presentation varied from 9% to 33%, [3][4][5][8][9][10][11] and confirms the particularly poor prognostic profile of patients in this trial (being at high risk of disseminated disease).…”
Section: Discussioncontrasting
confidence: 81%
“…Prognostic factors have been well described in previous reports [3][4][5][6][7][8][9][10][11][12] and a recent review by Goessling et al 13 summarizes these. In comparing these results with those reported in the literature, it is important to match the proportion of patients with adverse prognostic variables, the most important being the presence of nodal metastases.…”
Section: Discussionmentioning
confidence: 97%
“…The etiology of this malignancy is still unknown. Documented cases have reported MCC after radiation and immunosuppressive therapies, or in association with other cancers (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, cumulative data from small series have suggested that stage, size of the primary tumor, and gender may have an influence on survival, whereas the prognostic impact of anatomic location and age are more controversial. [5][6][7][8] Although various factors can determine the aggressiveness of PNCs, the capacity for invasion and metastasis of tumor cells, involving the degradation of components of basement membranes and the extracellular matrix, is certainly important. The matrix metalloproteinases (MMPs) are a large family of zinc-dependent proteolytic enzymes 9,10 involved in the degradation of different components of the extracellular matrix.…”
mentioning
confidence: 99%